2021
DOI: 10.1002/bjs.11970
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric surgery is expensive but improves co-morbidity: 5-year assessment of patients with obesity and type 2 diabetes

Abstract: Background Bariatric surgery can be effective in weight reduction and diabetes remission in some patients, but is expensive. The costs of bariatric surgery in patients with obesity and type 2 diabetes mellitus (T2DM) were explored here. Methods Population-based retrospectively gathered data on patients with obesity and T2DM from the Hong Kong Hospital Authority (2006–2017) were evaluated. Direct medical costs from baseline up… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Likewise, in the study of Swedish Obese Subjects (SOS) ( 14 ) the costs of medication used in diabetes treatment decreased significantly after bariatric surgery. In turn, Wu et al ( 29 ) demonstrated that for patients who had undergone bariatric surgery, the costs of diabetes drugs illustrate a U-shape curve. The costs of medication in patients after operation were shown to drop 2 years after surgery (€1752 in year 1 and €973 in year 2) and rise by year 5 (to €1836).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, in the study of Swedish Obese Subjects (SOS) ( 14 ) the costs of medication used in diabetes treatment decreased significantly after bariatric surgery. In turn, Wu et al ( 29 ) demonstrated that for patients who had undergone bariatric surgery, the costs of diabetes drugs illustrate a U-shape curve. The costs of medication in patients after operation were shown to drop 2 years after surgery (€1752 in year 1 and €973 in year 2) and rise by year 5 (to €1836).…”
Section: Discussionmentioning
confidence: 99%
“…Hong Kong's first bariatric surgery programme was established in 2002 at Prince of Wales Hospital, affiliated with The Chinese University of Hong Kong. 22 Encouraged by the success and safety of the early Prince of Wales Hospital obesity surgery service, 23 increasing numbers of public and private hospitals have begun to provide bariatric surgical interventions to obese patients in Hong Kong (Table ).…”
Section: Overview Of Bariatric and Metabolic Surgery In Hong Kongmentioning
confidence: 99%